Basic Features of Socialization of the Person - Nishanova Farida Mamasharifovna (Genius Journals, 2022)
This article discusses the socialization characteristics of the individual. The role of the individual in society is analyzed. The individual is seen as the driving force of society.
Keywords: Individual; Society; Social Environment; Development